Evaluation of inhibition activity of silver nanoparticles activity against pathogenic bacteria - Al-Bahrani , Rusol, M.; Ghafil, Jenan Atiyah (Iraqi Journal of Science, 2022)
Silver nanoparticles synthesized from aqueoes extract for mushroom pleurotus ostreatus. Silver nanoparticles were showing good antibacterial activity. The antibacterial activity conducted against different pathogenic bacteria such as Serratia marcescens, Pseudomonas fluorescens, Listeria, Methicillin-resistant Staphylococcus aureus (MARSA), Proteus mirabilis, Proteus vulgaris and Klebsiella pneumoniae. The maximum inhibition zone was observed against S. marcesance. However, the lowest inhibition zone was found against P. fluorescens.